Japanese Infertility Patients’ Attitudes towards Directed and Non-Directed Oocyte Donation: Analysis of a Questionnaire Survey and Implications for Public Policy - Yosuke Shimazono (NUS Press, 2018)
10.1353/asb.2013.0063